2016
DOI: 10.18632/oncotarget.10351
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of T790M mutation in EGFR-mutant lung adenocarcinoma patients having a history of acquired resistance to EGFR-TKI: focus on rebiopsy timing and long-term existence of T790M

Abstract: Different growth kinetics occurring between the sensitive and T790M-containing cells may result in the repopulation of tumor cells over time. Little information has yet been uncovered on whether rebiopsy timing influences the T790M detection rate. We enrolled a total of 98 epidermal growth factor receptor (EGFR)-mutant lung adenocarcinoma patients, who had a history of acquired resistance to EGFR-tyrosine kinase inhibitor (TKI) and available rebiopsy tumor specimens for reassessment of EGFR mutations. Rebiopsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 41 publications
(61 reference statements)
4
27
2
Order By: Relevance
“…The complication rate was 8.6% and mortality was 0.95%. T790M mutations were reported in 33.3% of cases, unlike previous reports that detected such mutations in approximately 50% of patients . We were unable to determine the specific characteristics related to T790M prevalence.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The complication rate was 8.6% and mortality was 0.95%. T790M mutations were reported in 33.3% of cases, unlike previous reports that detected such mutations in approximately 50% of patients . We were unable to determine the specific characteristics related to T790M prevalence.…”
Section: Discussionmentioning
confidence: 57%
“…T790M mutations are the most common acquired resistance mechanism, accounting for 50% to 63% of mutations . In this study, using the PNA Clamp method, only 33.9% of patients with sensitizing mutations exhibited T790M mutations.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This could be explained because a longer exposure to a TKI confers the time to develop a resistance mutation. Following this observation, previous studies have shown slower cell growth and favorable outcomes in patients with acquired resistance to EGFR-TKI associated to T790M mutations (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 68%
“…To date, mostly retrospective [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] and 2 prospective 46,47 Asian case series investigated clinical-pathologic characteristics of T790M mutant lung cancer. Only a few data are available in Caucasian patients, and none of these studies investigated clinical progression patterns related to T790M in detail.…”
Section: Introductionmentioning
confidence: 99%